SPIRTLER TEMASÍN INTERAKTIV METODLARDAN PAYDALANÍP OQÍTÍW - Abdisattarova, E.; Jarekeyeva, D. (SCIENCE and SOCIETY, 2025)
The article provides a brief description of teaching the topic “Alcohols” in organic chemistry using interactive methods. In the in-depth study of the organic chemistry course at school, interactive methods such as “Awa-Yaq”, Finding Formulas, T-Table, Venn Diagram are presented with examples related to the topic “Alcohols.”